Evaluation of the Antinociceptive Effect of Hydroalcoholic Extract of Potentilla Reptans L. in the Adult Male Rat - M Mahmoodi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2016)
Introduction: Medicinal plants have been a focus of attention to researchers due to their fewer side effects in treating diseases comared to chemical drugs. Some health properties of medicinal plants such as anti-hypercholesterolemia and antioxidant effects of Potentilla reptans have been proven. Therefore, the present study aimed to investigate the antinociceptive and analgesic effect of hydro-alcoholic extract of Potentilla reptans L. (HEP) in the male rat.